Genomic duplication resulting in increased copy number of genes encoding the sister chromatid cohesion complex conveys clinical consequences distinct from Cornelia de Lange. Issue 9 (3rd December 2008) - Yan, J; Zhang, F; Brundage, E; Scheuerle, A; Lanpher, B; Erickson, R P; Powis, Z; Robinson, H B; Trapane, P L; Stachiw-Hietpas, D; Keppler-Noreuil, K M; Lalani, S R; et al.
Abstract : Background: Cornelia de Lange syndrome (CdLS) is a multisystem congenital anomaly disorder. Heterozygous point mutations in three genes ( NIPBL, SMC3 and SMC1A ), encoding components of the sister chromatid cohesion apparatus, are responsible for ∼50–60% of CdLS cases. Recent studies have revealed a high degree of genomic rearrangements (for example, deletions and duplications) in the human genome, which result in gene copy number variations (CNVs). CNVs have been associated with a wide range of both Mendelian and complex traits including disease phenotypes such as Charcot–Marie–Tooth type 1A, Pelizaeus–Merzbacher, Parkinson, Alzheimer, autism and schizophrenia. Increased versus decreased copy number of the same gene can potentially cause either similar or different clinical features. Methods and results: This study identified duplications on chromosomes 5 or X using genome wide array comparative genomic hybridisation (aCGH). The duplicated regions contain either the NIPBL or the SMC1A genes. Junction sequences analyses revealed the involvement of three genomic rearrangement mechanisms. The patients share some common features including mental retardation, developmental delay, sleep abnormalities, and craniofacial and limb defects. The systems affected are the same as in CdLS, but clinical manifestations are distinct from CdLS; particularly the absence of the CdLS facial gestalt. Conclusions: The results confirm the notion that duplication CNV of genes can be a common mechanism for human genetic diseases. Defining the clinical consequences for a specific gene dosage alteration represents a new "reverse genomics" trend in medical genetics that is reciprocal to the traditional approach of delineation of the common clinical phenotype preceding the discovery of the genetic aetiology.